1996
DOI: 10.1016/s0022-5347(01)65578-2
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Venous Leakage: A Prospective Clinicopathological Correlation of Corporeal Function and Structure

Abstract: The pathophysiology of structurally based corporeal veno-occlusive dysfunction is related to elevated corporeal connective tissue content. Based on our data and those in the literature corporeal fibrosis is hypothesized to develop secondary to abnormalities in the regulation of normal collagen synthesis and degradation, most likely associated with adverse influences of chronic ischemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
203
0
5

Year Published

1998
1998
2011
2011

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 246 publications
(214 citation statements)
references
References 28 publications
6
203
0
5
Order By: Relevance
“…Negative control was performed by primary antibody omission (d) hemodynamic events: increased arterial inflow, sinusoidal SM relaxation, and decreased venous outflow. Thus, the mechanical properties of erectile tissue are strictly dependent on the integrity of its structure (Moreland 2000;Nehra et al 1996).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Negative control was performed by primary antibody omission (d) hemodynamic events: increased arterial inflow, sinusoidal SM relaxation, and decreased venous outflow. Thus, the mechanical properties of erectile tissue are strictly dependent on the integrity of its structure (Moreland 2000;Nehra et al 1996).…”
Section: Discussionmentioning
confidence: 99%
“…They provide substantial evidence that long-standing androgen deprivation, either physiologically, as it occurs in aging, or following pharmacological treatment, leads to cavernous tissue remodeling that results in a replacement of SM cells by fibroblasts, increase in collagen deposition, and reduction of the SM-to-CT ratio. The consequent change in fibroelastic properties of penile tissue compromises the compliance and hemodynamics, results in corporeal veno-occlusive dysfunction (Nehra et al 1996) and decreased capacity of sinuses to fill with blood, and produces an effective erection (Ferrer et al 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result of diabetes, progressive replacement of cavernosal smooth muscle by fibrosis may lead to complete erectile failure (53). Effective surgical interventions in such cases are limited to penile implants.…”
Section: Male Sexual Dysfunctionmentioning
confidence: 99%
“…7±11 In a prospective study of men undergoing penile prosthesis insertion, we have found a direct correlation between erectile function and the ratio of trabecular smooth muscle to total erectile tissue. 2 Erectile function was de®ned by experimentally determined parameters of¯ow to maintain erection, resistance to ®lling, and pressure decay using dynamic infusion corpus cavernosography/cavernosometry (DICC) 12 ow-to-maintain values (50 ±120 ml/min) and substantial cavernous leakage. Similar relationships were found when out¯ow resistance and pressure decay were correlated with percent trabecular smooth muscle.…”
Section: Introductionmentioning
confidence: 99%